An introduction to Arabic literature - Allen, Roger, 1942- (Cambridge University Press, 2000)
This volume provides a comprehensive introductory survey of literary texts in Arabic, from the fifth century to the present day. With extensive quotations in translation, a chronology and a guide to further reading, it is an invaluable student introduction to a major non-Western literary tradition.